Study of the Properties of Image Formation by an Optical System Consisting of a Diffractive Lens - Khuder, Raghda Z.; Hasan, Alaa B. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Diffractive lenses form images based on the principle of light diffraction, unlike conventional lenses that rely on the phenomenon of refraction to form images. Diffractive lenses consist of precisely aligned structures of holes or slits that act as optical gratings. They are arranged to give the lens the optical property of changing the path of incident rays, creating an image pattern similar to that of conventional lenses. This work aims to study the image characteristics formed by diffractive lenses by conducting a computer simulation in the Zemax optical design software. The analysis tools available in the software are then used to study the quality of the resulting image and evaluate the performance of the diffractive lens. The results show that the image characteristics formed by diffractive lenses are similar to those of conventional lenses. These results indicate the image-forming performance of diffractive lenses. This gives designers flexibility in lens design, in terms of the type and number of slits used without the use of spherical surfaces